Leading rich media implementation collaboratively : mobilising international, national and business expertise : final report. - Smyth, Robyn; Andrews, Trish; Bordujenko, Jason; Caladine, Richard; Vale, Deborah (Australian Learning and Teaching Council, 2011)
The Leading Rich Media Technologies Collaboratively project began late in 2007 with the aim of contributing to improved teaching and learning outcomes and increased institutional efficiency and effectiveness by providing frameworks for decision-making about the use of rich media technologies which will be applicable to its use in learning, teaching, administration and research. This report provides an overview of the work completed by the project partners. It is divided into six parts with Part One providing an outline of the project and its processes. The chronological annotated bibliography is summarised in Part Two. Part Three contains the reports resulting from the data gathering using surveys undertaken during the project. Case studies carried are contained in Part Four. The conclusions and recommendations of the project team for the use of rich media technologies in the higher education sector are contained in Part Five. Part Six lists all other forms of dissemination. [Executive summary, ed]